Unleashing digital transformation to achieve the sustainable development goals across multiple sectors - Varriale, Vincenzo; Camilleri, Mark Anthony; Cammarano, Antonello; Michelino, Francesca; Müller, Julian; Strazzullo, Serena (Sustainable Development, 2024)
Digital technologies have the potential to support achieving the Sustainable Development Goals (SDGs). Existing scientific literature lacks a comprehensive analysis of the triple link: “digital technologies – different industry sectors – SDGs”. By systematically analyzing extant literature, 1098 sustainable business practices have been collected from 578 papers, using 11 digital technologies in 17 industries to achieve the 17 SDGs. For instance, find that artificial intelligence can be used to achieve affordable and clean energy (SDG 7), responsible consumption and production (SDG 12) as well as to address climate change (SDG 13). Further, geospatial technologies may be applied in the agricultural industry to reduce hunger in various domains (SDG 2), to foster good health and well-being (SDG 3), to improve the availability of clean water and sanitation facilities (SDG 6), raise awareness on responsible consumption and production (SDG 12), and to safeguard life on land (SDG 15), among other insights.
Created from Fastlane, Scopus look-up
Keywords: artificial intelligence; blockchain; digital transformation; sustainability; sustainable development goals